The Mystery of Edwin Drood - Dickens, Charles, 1812-1870 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Mystery of Edwin Drood" by Charles Dickens is a novel published in 1870. Dickens's final and unfinished work centers on John Jasper, a cathedral choirmaster and opium addict who desires his pupil Rosa Bud the fiancée of his nephew Edwin Drood. When Edwin vanishes mysteriously after a tense reconciliation dinner with his rival Neville Landless, suspicion falls on Neville while Jasper's dark obsessions deepen. Set in the cathedral town of Cloisterham, this mystery remains unsolved, as Dickens died before revealing its conclusion. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Mystery_of_Edwin_Drood
Release date is 1996-06-01
Keywords: England -- Fiction; Psychological fiction; Triangles (Interpersonal relations) -- Fiction; Cathedrals -- Fiction; Missing persons -- Fiction; Choral conductors -- Fiction; Separation (Psychology) -- Fiction; Mystery fiction